Analisis Efektivitas Promosi Pada Media Sosial Instagram PT. Sejahtera Wahana Gemilang: indonesia - Ilvan Adi Pratama; Triana Setiyarini (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
Many business people in today's era have taken advantage of technological advancements by marketing their products and services via the internet. The use of social media for promotional activities has increased in line with the increase in the number of internet users each year, Particularly via social media platforms. Instagram is widely recognised as a prevalent social media platform utilised for promotional purposes. This particular platform of social media is the most numerous and is considered the most effective as a means of promotion. PT.Sejahtera Wahana Gemilang has also been promoting its products on its Instagram social media account @ea.surabaya in recent years. however, from the author's observation, these media accounts show a lack of activity in promoting their products. Therefore the author wants to know how effective the Instagram @chitose.surabaya social media account is in carrying out marketing promotions based on the AIDA strategy approach. The present study employs qualitative research techniques and examines multiple case studies. The findings of this investigation suggest that the promotional efforts of the Instagram handle @chitose.surabaya are yet to yield desired outcomes in terms of garnering attention, generating interest, stimulating desire, and inducing action or AIDA strategy approach on the Instagram social media account @chitose.surabaya in attracting potential consumers to buy the product being promoted.